Additive Manufacturing of Knee Joint Implants: Design, Fabrication, and Performance Analysis - Rupesh Sijoriya; Dharmesh Barodiya; Chinmay Saraf (International Journal of Solid State Innovations & Research, 2024)
These days, the number of knee joint failures is rising daily due to factors like pollution, big accidents, poor diet, which weakens the bone, and lack of rest. One of the main joints in the human body is the knee. Metals are utilised to repair damaged surfaces in knee joint surgery. More than 800,000 knee implants are used worldwide, and now various advanced manufacturing methods are used for its production. One of the most common methods that is used for manufacturing knee implants is metal additive manufacturing. It is critical to understand the manufacturing and analysis of knee implants to improve its design and reduce cost. This literature reviews studies on additive manufacturing and analysis of knee joints. The number of knee replacement procedures is rising daily. As the number of knee replacement procedures rises and engineering technology advances, more models are being created to better suit patient needs. Artificial knee components composed of various materials are used to replace the failed knee joint.
Keywords: Additive manufacturing; Finite element analysis; knee implants; stress